Blood sampling in doping control. First experiences from regular testing in athletics - Birkeland, K. I.; Donike, M.; Ljungqvist, A.; Fagerhol, M.; Jensen, J.; Hemmersbach, P.; Oftebro, H.; Haug, E. (International Journal of Sports Medicine, 1997)
We report the results from blood sampling taken for the first time during doping control in athletics. The study includes samples from 99 athletes tested during IAAF-meetings in 1993-94. Blood doping with allogenic blood was not detected. The distribution of haemoglobin levels in athletes did not differ markedly from that found in controls. Erythropoietin (EPO) values were markedly lower in athletes than in controls, and 58% had EPO lower than the detection limit for the assay. This may be due to high-altitude residence prior to testing. Measurements of growth hormone (GH) and insulin-like growth factor 1 did not suggest GH-misuse in any athlete tested. One third of the male athletes had testosterone levels that were lower than the normal reference interval. This may at least partly be due to the combination of sampling at night and after strenuous exercise. One female athlete was found to have a grossly elevated testosterone level. In conclusion, the present results show the importance of taking into account the special circumstances during sampling when interpreting results from blood testing in athletes. Future research should focus on developing more sensitive and specific tests to detect doping with endogenous substances such as GH and EPO.